2006
DOI: 10.1074/jbc.m512064200
|View full text |Cite
|
Sign up to set email alerts
|

Leucine 135 of Tropomodulin-1 Regulates Its Association with Tropomyosin, Its Cellular Localization, and the Integrity of Sarcomeres

Abstract: Tropomodulin-1 (Tmod-1) is a well defined actin-capping protein that interacts with tropomyosin (TM) at the pointed end of actin filaments. Previous studies by others have mapped its TM-binding domain to the amino terminus from amino acid 39 to 138. In this study, we have identified several amino acid residues on Tmod-1 that are important for its interaction with TM5 (a nonmuscle TM isoform). Glutathione S-transferase affinity chromatography and immunoprecipitation assays reveal that Tmod sense mutations of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 29 publications
(36 reference statements)
2
27
1
Order By: Relevance
“…Original evidence of a second TM binding site was shown in the ability of 125 I-labeled erythrocyte TM (a heterodimer of α and γ short TM) to bind to Tmod1 95-359 immobilized on nitrocellulose (28). Since we began our work, Vera et al (29) mapped a binding site for TM5 (a short erythrocyte TM encoded by the γ-TM gene) to residues 105-127 and Kong et al (42) found that residues L134 and L135 are crucial for TM5 binding. However, all three studies used qualitative assays to measure interaction, methods that were unable to quantify the affinity or stoichiometry of the complex.…”
Section: Discussionmentioning
confidence: 99%
“…Original evidence of a second TM binding site was shown in the ability of 125 I-labeled erythrocyte TM (a heterodimer of α and γ short TM) to bind to Tmod1 95-359 immobilized on nitrocellulose (28). Since we began our work, Vera et al (29) mapped a binding site for TM5 (a short erythrocyte TM encoded by the γ-TM gene) to residues 105-127 and Kong et al (42) found that residues L134 and L135 are crucial for TM5 binding. However, all three studies used qualitative assays to measure interaction, methods that were unable to quantify the affinity or stoichiometry of the complex.…”
Section: Discussionmentioning
confidence: 99%
“…We also introduced four mutations (L29G, L73D, L134D, and L138V) that were reported previously to disrupt each of the three functional ␣-helices in N-terminal half of Tmod3 (supplemental Fig. S1) (29,30,44). We tested the ability of Tmod3 mutant proteins to bind G-actin by performing chemical cross-linking assays with the zero-length cross-linker, EDC/sulfo-NHS, followed by SDS-PAGE and Coomassie staining.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, disruption of each tropomyosin-binding site by introducing a point mutation in ␣-helix1 or ␣-helix3 of Tmod3 has no effect on its actin-nucleating activity (Fig. 7 and data not shown) while completely abolishing its tropomyosin binding and tropomyosin-dependent actin capping activities (29,30,44). However, it is possible that tropomyosin could bind to the N-terminal domain of a Tmod whose C-terminal domain caps the pointed end of an actin nucleus, which then may further bind and stabilize actin filament growth from that nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In striated muscle, in cooperation with tropomyosin, Tmod1 binds to and limits the exchange of actin monomers at the pointed end of the actin thin filaments (Weber et al, 1994). The localization and capping functions of Tmod1 appear to be dependent on two actin-binding and two tropomyosin-binding domains, given that mutations in any of these regions affect these functions Kostyukova et al, 2005;Kostyukova et al, 2006;Greenfield et al, 2005;Kong and Kedes, 2006;Tsukada et al, 2011). Overexpression of Tmod1 in primary myocyte cultures results in a shortening of actin filaments (Sussman et al, 1999;Littlefield et al, 2001), whereas depletion of Tmod1 leads to abnormally long thin filaments (Gregorio et al, 1995;Sussman et al, 1998;Mudry et al, 2003).…”
Section: Introductionmentioning
confidence: 99%